Fundamentals of corporate finance - Brealey, Richard A.; Myers, Stewart C.; Marcus, Alan J. (The McGraw-Hill education series in finance, insurance, and real estate, 2023)
"This book is an introduction to corporate finance. It focuses on how companies invest in real assets, how they raise the money to pay for the investments, and how those assets ultimately affect the value of the firm. It also provides a broad overview of the financial landscape, discussing, for example, the major players in financial markets, the role of financial institutions in the economy, and how securities are traded and valued by investors. The book offers a framework for systematically thinking about most of the important financial problems that both firms and individuals are likely to confront".